Profile of Primary Arteriovenous Fistula Failure in End-Stage Renal Disease Patients on Hemodialysis at Dr. Soetomo General Academic Hospital, Surabaya - Reviano, Moses Orvin; Sembiring, Yan Efrata; Widodo, Widodo; Soebroto, Heroe (Universitas Airlangga, 2025)
Highlights: Arteriovenous fistula is preferred for dialysis vascular access. Twenty-eight (4.8%) cases had primary arteriovenous fistula failure. Abstract Introduction: Primary arteriovenous fistula failure in Indonesia is still relatively high, and end-stage renal disease patients are prioritized to have arteriovenous fistula as their main vascular access for hemodialysis. This study aimed to determine the primary arteriovenous fistula failure profile in end-stage renal disease patients on hemodialysis at Dr. Soetomo General Academic Hospital, Surabaya. Methods: This was a descriptive retrospective study. The population was primary arteriovenous fistula failure patients. A total sampling method was used from the medical records of Dr. Soetomo General Academic Hospital, Surabaya, from January 2021 until January 2023. The research variables were gender, age, diabetes mellitus (DM) history, hypertension (HTN) history, duration of catheter double-lumen (CDL) usage before arteriovenous fistula placement, incidence of early thrombosis, and incidence of maturation failure. Data was analyzed with Microsoft Excel 2018. Results: There were 28 primary arteriovenous fistula failure cases from 580 surgical procedures performed in the research period (4.8%). The dominant results were: 15 female patients (54%), 25 non-elderly patients (89%), 16 non-DM patients (57%), 14 patients in both HTN and non-HTN (50%), 20 prolonged CDL patients (71%), followed by 7 patients that did not use CDL (25%), 28 maturation failure patients (100%), and 18 non-early thrombosis patients (64%). Conclusion: Female gender, duration of CDL usage, and maturation failure were the more prominent characteristics in this research profile. Meanwhile, the less prominent characteristics were old age, DM history, HTN history, and early thrombosis.